2019
DOI: 10.1186/s12917-019-1981-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of time-series models for monitoring temporal trends in endemic diseases sero-prevalence: lessons from porcine reproductive and respiratory syndrome in Danish swine herds

Abstract: Background Monitoring systems are essential to detect if the number of cases of a specific disease is rising. Data collected as part of voluntary disease monitoring programs is particularly useful to evaluate if control and eradication programs achieve the target. These data are characterized by random noise which makes harder to interpret temporal changes in the data. Monitoring trends in the data is a possible approach to overcome this issue. The objective of this study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…However, comparison of results from the 2013 UK survey 8 with those from the 2012−2013 Scottish survey undertaken at a similar time indicates that the proportion of PRRSV seropositive farms was lower in Scotland. Compared with the median seroprevalence reported from 2010 to 2014 in Denmark, 32 the proportion of farms infected with PRRSV inferred from all three surveys is higher in Scotland. However, these studies used different methods which compromise a direct comparison.…”
Section: Discussioncontrasting
confidence: 61%
“…However, comparison of results from the 2013 UK survey 8 with those from the 2012−2013 Scottish survey undertaken at a similar time indicates that the proportion of PRRSV seropositive farms was lower in Scotland. Compared with the median seroprevalence reported from 2010 to 2014 in Denmark, 32 the proportion of farms infected with PRRSV inferred from all three surveys is higher in Scotland. However, these studies used different methods which compromise a direct comparison.…”
Section: Discussioncontrasting
confidence: 61%
“…A univariate dynamic linear model (DLM) with a local linear trend component, as described in detail by West and Harrison (11) and applied in previous studies (12)(13)(14)(15), was used to model data at the herd level. A previous study showed that Bayesian forecasting methods adapt faster to changes in the data, compared to the deterministic Holt's linear trend methods for monitoring trends of time-series (14). The general aim of a DLM is to estimate the underlying true value of a given variable, which is expected to change over time.…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
“…where m t is the filtered mean of the antimicrobial consumption at time t and T t is the local linear trend at time t. This local linear trend was incorporated into the model to allow the system to adapt to a possible positive or negative growth in antimicrobial consumption as follows the example given in previous studies (13)(14)(15). A detailed description of the full model, as well as the R code, can be found in the literature (15).…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
“…Time-series analysis using inspection data is very useful for objectively understanding the fattening process on farms. In fact, several studies have conducted time-series analyses of livestock diseases and production quantity [5,6,7]. Other studies have analyzed diseases of livestock in slaughterhouses using predictive models [8, 9,10,11].…”
mentioning
confidence: 99%